ОСОБЛИВОСТІ ЦУКРОЗНИЖУВАЛЬНОЇ ДІЇ СУХОГО ЕКСТРАКТУ З КОРЕНІВ І КОРЕНЕВИЩ ОМАНУ ВИСОКОГО ЗАЛЕЖНО ВІД ДОЗИ - Ежнед, М. А.; Грошовий, Т. А.; Горошко, О. М. (Фармацевтичний часопис, 2015)
features of hypoglycemic effect of dry extract from the Elecampane roots and rhizomes depending on the dose. М.А. Ezhned1, Т.А. Groshovyi2, О.М. Goroshko1 BukovinianStateMedical University1, Chernivtsi I.Ya.GorbachevskyiTernopilStateMedical University2, Ternopil Summary: in an experiment on rats was established a dose dependency action of Elecampane dry extract of roots and rhizomes in 1% of starch with a single use on a glucose load. It was found that the glucose-lowering effect of the dry extract of theElecampane roots and rhizomes better manifested at a dose of 0.11 mg /kg. Keywords: elecampane, extract, glucose load, hypoglycemic effect. Introduction. In the structure of endocrine diseases diabetes mellitus (DM) constitutes about 60-70%. The frequency of DM vary from 1,5 to 3% on an average increasing in the developed countries of the world (up to 5-6%). Therefore, morbidity of DM remains a big problem both inUkraineand in the world practice. That’s why the search of new medicines is rather topical. Today pharmaceutical market presents a wide store of synthetic medical preparations used for the control and treatment of patients with DM. The plants that may be a potential source of hypoglycemic means and widely used in traditional medicine to prevent DM can be an alternative to synthetic preparations. Hypoglycemic effect of 70% extract of Inula viscosa has been determined in the experiment. The following stage of the study is to determine dose-dependent action. Objective. To determine the effect of an increasing dose of a dry extract made of the roots and rhizome of Inula viscosa upon hypoglycemic action. Materials and methods. A dry extract of the roots and rhizomes of Inula viscosa was studied in 1% of starch paste. Reference therapeutic dose for a rat was found to be 0,08 - 0,2 mg/kg. The medicinal herbal tea “Arfazetin” (the producer – CC “Liktravy”, Zhytomyr), a single plant medical preparation with a proved hyperglycemic activity, which is registered and allowed to be used in Ukraine, was taken as a preparation for comparison as an infusion in the dose of 24 ml/kg. The animals were divided into 7 groups. The 1st group was the control, all other groups received a dry extract of Inula viscosa in the dose of 0,1 mg/kg (2 experimental group); 0,11 mg/kg (3 group); 0,12 mg/kg (4 group); 0,15 mg/kg (5 group); 0,2 mg/kg (6 group); the infusion of the medicinal herbal tea “Arfazetin” in the dose of 24 ml/kg (7 group). Glucose concentration in the blood was detected by means of glucose-oxidase method with the set of reagents of the firm “Filicit-Diagnostika”. Results and discussion. Intra-peritoneal introduction of glucose in the dose of 3 g/kg resulted in the development of acute hyperglycemia manifested a reliable increase of glucose level in all the groups of animals as compared to the initial data. Thus, the initial glucose level in rats was in 2,17 times higher as compared to the control group. Hypoglycemic action increased with the increase of Inula viscosa dose, which was maximal as 46,08% in case of injecting in the dose of 0,11 mg/kg. With an increasing dose of a dry extract of Inula viscosa hypoglycemic action decreased. Thus, in case of injecting Inula viscosa extract in the dose of 0,12 mg/kg hypoglycemic action was 23,53%, in the dose of 0,15 mg/kg - 24,61% respectively, and in the dose of 0,2 mg/kg there is only a tendency to decreased action which is indicative of unreliability of the results.